Pengaruh kepemilikan NPWP terhadap kepatuhan wajib pajak pada Kantor Pelayanan Pajak Pratama Manado - Dama, Aditya; Saerang, David Paul Elia; Gamaliel, Hendrik (Indonesia Accounting Journal, 2019)
Income tax can be used for various functions of determining policies related to income. Taxpayer compliance is strongly influenced by the ownership of a country's NPWP because if a Taxpayer is not compliant it will cause reduced tax revenue. The object of this research is the Income Taxpayer which is limited to the Corporate Income Taxpayer in the city of Manado. The purpose of this study is to determine whether NPWP ownership has an effect on tax compliance at the Manado Primary Tax Service Office. In conducting this research a statistical analysis tool is used that is simple linear regression analysis and is strengthened by testing the hypothesis that is the t test. The results showed the regression model obtained was Y = 10.895 + 0.299 X. The constant a of 10.895 gives the sense that if the Income Tax Audit is perceived to be constant or equal to zero (0), then the magnitude of Taxpayer Compliance is 10.895 units. Furthermore, the value of b which is a regression coefficient of variable X (NPWP ownership) of 0.299 means that if NPWP ownership has increased by one (1) unit, then the amount of income tax increase has increased or increased by 0.299 units assuming the other variables are fixed or constant. Taxpayers compliance (Y) got contribution from NPWP (X) ownership factor of 6.6%, while the rest was explained by other variables not included in this study. Thus it is known that NPWP ownership has no significant effect on increasing taxpayer compliance.